Guru Matematika Hebat: Perspektif Siswa dalam Pembelajaran Berbasis Teknologi - Putranto, Sumbaji (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
After the Covid-19 pandemic, the impact of life on the economic, social, health, and education sectors is still being felt. One of the changes in education is the increasing number of technology-based learning. This research aims to find out students' perspectives on online learning, the technology used by teachers in learning, and online learning strategies based on students' perspectives. Researchers use phenomenological research. Researchers began collecting data using a questionnaire followed by semi-structured interviews. Data analysis was carried out using the Bogdan & Biklen approach including data reduction, categorization of data into sub-themes and themes, deduce. The research shows that students have difficulty understanding mathematics when learning online. The use of technology that is not optimal causes impacts. Teachers do not take advantage of virtual meetings which can be a medium for meetings between students and teachers, so that both can build communication and closeness between teachers and students which will help students understand mathematics material.